OnabotulinumtoxinA for the treatment of neurogenic detrusor overactivity in children. Issue 1 (11th December 2020) - Austin, Paul F.; Franco, Israel; Dobremez, Eric; Kroll, Pawel; Titanji, Wilson; Geib, Till; Jenkins, Brenda; Hoebeke, Piet B.
Abstract: Aims: This study evaluated whether one (or more) of three doses of onabotulinumtoxinA were safe and effective to treat neurogenic detrusor overactivity (NDO) in children. Methods: This was a 48‐week prospective, multicenter, randomized, double‐blind study in children (aged 5–17 years) with NDO and urinary incontinence (UI) receiving one onabotulinumtoxinA treatment (50, 100, or 200 U; not to exceed 6 U/kg). Primary endpoint: change from baseline in daytime UI episodes. Secondary endpoints: change from baseline in urine volume at first morning catheterization, urodynamic measures, and positive response on the treatment benefit scale. Safety was also assessed. Results: There was a similar reduction in urinary incontinence from baseline to Week 6 for all doses (−1.3 episodes/day). Most patients reported positive responses on the treatment benefit scale (75.0%−80.5%). From baseline to Week 6, increases were observed in urine volume at first morning clean intermittent catheterization (50 U, 21.9 ml; 100 U, 34.9 ml; 200 U, 87.5 ml; p  = 0.0055, 200 U vs. 50 U) and in maximum cystometric capacity (range 48.6−63.6 ml) and decreases in maximum detrusor pressure during the storage phase (50 U, −12.9; 100 U, −20.1; 200 U, −27.3 cmH2 O; p  = 0.0157, 200 U vs. 50 U). The proportion of patients experiencing involuntary detrusor contractions dropped from baseline (50 U, 94.4%; 100 U, 88.1%; 200 U, 92.6%) to Week 6 (50 U, 61.8%; 100 U, 44.7%; 200 U, 46.4%). Safety was similar across doses; urinary tract infection was most frequent. Conclusions: OnabotulinumtoxinA was well tolerated and effective for the treatment of NDO in children; 200 U showed greater efficacy in reducing bladder pressure and increasing bladder capacity.